Determinação de 2-naftilamina em amostras de perfume utilizando eletrodo de diamante dopado com boro - Rodrigues, Guilherme Nunes (2019)
Aromatic amines are compounds with activities that are proven to be harmful to humans. Among them, 2-naphthylamine (2NAP) is one of the 120 species with proven carcinogenic action, being responsible for cases of bladder cancer. It may be used as a precursor in the synthesis of various azo dyes and has been banned in many parts of the world. The methods of chromatography coupled with mass spectrometry are the most often used in the monitoring of this amines, showing limit of detection at picogram levels. Electrochemical techniques are an alternative to these methods and have the advantage of lower cost instrumentation and high analytical frequency, despite the higher limit of detection. This work presents a simple electrochemical method for 2NAP determination in perfume by differential-pulse voltammetry (DPV) employing a boron-doped diamond (BDD) electrode cathodically treated. Simple dilution of sample in supporting electrolyte was performed before electrochemical analysis. A borate buffer solution of pH 10.0 containing 20% (v/v) ethanol provided stable responses of 2NAP without electrode passivation. Modulation time, potential step and modulation amplitude were optimized at 20 ms, 6 mV and 70 mV, respectively, which achieved a limit of detection (LOD) of estimated as 4.6 nmol L−1 with a linear range between 0.5 and 90 μmol L−1, and RSD < 2.9%. The analyzed perfume sample presented 2NAP concentration below the LOD value. Recovery values for spiked sample with 2NAP were between 102 and 104%. The proposed method is feasible to be applied for 2NAP detection and quantification on perfume samples with simple sample preparation.